E-Learning Proposal System in Public Secondary School Learning - Damuri, Amat; Isnain, Nasrulloh; Rahmatika, Rahmatika; Priyatama, Abednego; Irawan Chandra, Yudi; Syah Putra, Arman (International Journal of Educational Research & Social Sciences, 2021)
Abstract The background of this research is to know how the e-learning system in the teaching and learning system at the public high school level, because the Covid 19 pandemic still allows us to learn online at home, with the e-learning system, the learning system can be very effective. remotely, because this research this time will discuss how a good system is applied to the learning process with an e-learning system. The method used in this research is to use the literature review method by referring to previously published books and journals, with the existence of books and journals that discuss this research before, it is certain that this research will produce the latest research and can become the basis for future research. . There are many remote learning method systems during the Covid 19 pandemic, with this remote learning system, the spread of the Corona virus will be greatly reduced, because students do not meet in person and cannot spread directly through physical contact, with the distance learning method. the teaching and learning system continues even though the Covid 19 pandemic spreads. In this research, we will produce a system proposal that will be the basis for the development of distance teaching and learning methods, using e-learning media at an educational level, namely public high schools with a proposed system, so it can be the best suggestion in the future. thiscovid 19 pandemic. Keyword: E-learning, Learning, High School, Online.